Quantifying the High-Temperature Separation Behavior of Lamellar Interfaces in γ-Titanium Aluminide Under Tensile Loading by Molecular Dynamics - Ganesan, Hariprasath; Scheider, Ingo; Cyron, Christian J. (Frontiers in Materials, 2021)
γ-titanium aluminide (TiAl) alloys with fully lamellar (FL) microstructure possess excellent properties for high-temperature applications. Such FL microstructure has interfaces at different length scales. The separation behavior of the lamellae at these interfaces is crucial for the mechanical properties of the whole material. Unfortunately, quantifying it by experiments is difficult. Therefore, we use molecular dynamics (MD) simulations to this end. Specifically, we study the high-temperature separation behavior under tensile loading of the four different kinds of lamellar interfaces appearing in TiAl, namely, the γ/α2 , γ/γPT , γ/γTT , and γ/γRB interface. In our simulations, we use two different atomistic interface models, a defect-free (Type-1) model and a model with preexisting voids (Type-2). Clearly, the latter is more physical, but studying also the former helps to understand the role of defects. Our simulation results show that among the four interfaces studied, the γ/α2 interface possesses the highest yield strength, followed by the γ/γPT, γ/γTT , and γ/γRB interface. For Type-1 models, our simulations reveal failure at the interface for all γ/γ interfaces but not for the γ/α2 interface. By contrast, for Type-2 models, we observe for all the four interfaces failure at the interface. Our atomistic simulations provide important data to define the parameters of traction-separation laws and cohesive zone models, which can be used in the framework of continuum mechanical modeling of TiAl. Temperature dependent model parameters were identified, and the complete traction-separation behavior was established, in which interface elasticity, interface plasticity and interface damage could be distinguished. By carefully eliminating the contribution of bulk deformation from the interface behavior, we were able to quantify the contribution of interface plasticity and interface damage, which can also be related to the dislocation evolution and void nucleation in the atomistic simulations.